Isolation and Molecular Characterization of Peste des Petits Ruminants Virus from Outbreaks in Southern Ethiopia, 2020 - Abde Aliy Mohammed; Tesfaye Rufael Chibssa; Waktole Terfa; Fasil Aklilu; Delesa Damena; Redeat Belayneh; Menbere Kidane (Advances in Virology)
Peste des petits ruminants (PPR) is one of the most important transboundary diseases of small ruminants. In this study, nasal and oral swabs (n = 24) were collected from sheep (n = 7) and goats (n = 17) with clinical signs in southern Ethiopia in March 2020. PPR virus was isolated on Vero dog cells expressing the signaling lymphocyte activation molecule (VDS) and screened using RT-qPCR. Positive samples were confirmed by conventional RT-PCR followed by sequencing of a partial nucleoprotein (N) gene segment. Results revealed that 54% (n = 13/24) of the tested samples were PPRV-positive Phylogenetic analysis revealed that the viruses belonged to lineage IV and lineage II. The lineage IV viruses were similar, although not identical, to other lineage IV viruses previously reported in Ethiopia and other East African countries while the lineage II viruses have been reported for the first time in Ethiopia showed a high nucleotide identity (99.06%) with the vaccine (Nigeria 75/1) that is currently used in Ethiopia for the prevention of PPR. Further investigations are therefore recommended in order to fully understand the true nature of the lineage II PPRVs in Ethiopia.